1968
DOI: 10.1172/jci105724
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alpha adrenergic blockade and tissue catecholamine depletion on pulmonary vascular response to hypoxia

Abstract: A B S T R A C T The highly reactive pulmonary vascular bed of the neonatal calf was utilized to determine whether the hypoxic pulmonary pressor response is modified by a-adrenergic blockade with phenoxybenzamine (Group A) or by tissue catecholamine depletion with reserpine (Group B). In addition, in Group A, the effects of hypoxia on the pulmonary circulation were compared and contrasted with those of l-norepinephrine (a-receptor stimulator) and isoproterenol (,8-receptor stimulator).In Group A, changes in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 22 publications
0
20
1
1
Order By: Relevance
“…The findings of a 1968 study by Silove and Grover demonstrated that an α-adrenergic blockade abolished the pulmonary vasoconstrictor responding to noradrenaline but not to hypoxia [18]. That is, hypoxiainduced pulmonary vasoconstriction cannot be impaired by sympathetic blockade.…”
Section: Discussionmentioning
confidence: 97%
“…The findings of a 1968 study by Silove and Grover demonstrated that an α-adrenergic blockade abolished the pulmonary vasoconstrictor responding to noradrenaline but not to hypoxia [18]. That is, hypoxiainduced pulmonary vasoconstriction cannot be impaired by sympathetic blockade.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that venoarterial or alveolarvascular reflexes confined to the lungs may be important in HPV (Fishman, 1976). Studies of HPV investigating the role of the autonomic nervous system have commonly used conventional antagonists of the parasympathetic and sympathetic components (Silove & Grover, 1968;Lewis, 1976). Burnstock (1972a) has proposed the 'purinergic hypothesis' that a purine nucleotide, probably ATP, is the principal transmitter released from nonadrenergic, noncholinergic 'purinergic' nerves.…”
Section: Tissue Preparationmentioning
confidence: 99%
“…We could not, however, confirm their findings; regional pulmonary perfusion responses after fl-blocking were similar to those during the control period, but (-blocking did prevent the effect of isoproterenol from relieving the regional hypoxic vasoconstriction. Silove and Grover (1968) stated that hypoxic vasoconstriction is not mediated through adrenergic receptor stimulation because the increase in pulmonary vascular resistance induced by hypoxia was not diminished by a-blockade. Malik and Kidd (1973) stated that the pulmonary vascular response to hypoxia in the intact dog is not under sympathetic control, and that the response to hypoxia is a local one.…”
Section: Effect Of Propranolol Per Sementioning
confidence: 99%